The effect of POFA as cement replacement material towards thermal insulation of aerated concrete - Intan Shuhada, Mustafa (2014)
Malaysia is one of the biggest countries of palm oil producer and exporter in the world. Millions tonnes of industrial waste such as palm oil fuel ash (POFA) is being produced every year with no commercial return on it. Base on pozzolanic behaviour possessed by POFA, it is necessary when POFA is being processed and used in the production of lightweight foamed concrete (LFC). Thus, the main focus of this research is to study the effect of palm oil fuel ash (POFA) towards water absorption, permeability and thermal conductivity of foamed concrete with 1200 kg/m' density.There are four type of foamed concrete were prepared namely i) POFA-0 with 100 % cement content, ii) POFA- 1 with 10 % POFA replacement of cement content, iii) POFA-2 with 20 % POFA replacement of cement content and iii) POFA-3 with 30 % POFA replacement of cement content. The specimens were water cured before being test. The result shows POFA-2 with 20 % POFA replacement of cement content produced highest compressive strength with 17.27 Mpa for 7 days curing period, 20.89 Mpa for 28 days curing period and 29.2 Mpa for 60 days curing period while thermal conductivity gives the lowest result which is 0.59 W/mk. As conclusion, 20 % of POFA replacement by total cement weight is an optimum percentage that is suitable to be used as pozzolamc replacement material of lightweight foamed concrete in industrial construction as this material is economic and environmental friendly